(3efGgL GdacQ heHGgL GdYHQs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW , J (B718 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CQSd LhO LhOI Ydi GdGfGe hHYO agPG Gdaf GdKGdK GdPi OYJ GdfaS Edi LeYgG s
(3BNQgG (B:s
(3hbGd CHh GdaJM cTGLe fUa GdTYQ GjVkG ef cGf fMh UjOg GdaVGA dJQGg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Gdaf GdKGdKs
(3hjfbSe Edi JSYI GHhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B42s
Keywords: (3eJaQbGJs